Physical Education and Health Teaching Behavior Realistic Dilemma and Optimization Path Research - Zhang, Shuaishuai; Song, Zhengyi; Li, Xuan; Li, Luzhen (Pacific International Journal, 2024)
This paper explores the crucial role of physical education (PE) in fostering students’ physical fitness and overall development, with a focus on the teaching behaviors of physical education teachers. These behaviors encompass a wide range of actions and activities that occur before, during, and after class, aiming to achieve effective teaching objectives. The connotation of PE teachers’ teaching behavior is categorized into speech acts and activity acts, encompassing both verbal and non-verbal actions. This study delves into the challenges faced by physical education teachers and proposes strategies for optimizing their teaching behaviors to cater better to students’ interests and aptitudes. It highlights the significance of teachers’ reflective behaviors in improving teaching quality and emphasizes the need for evaluating PE teachers’ teaching behavior to enhance overall teaching quality and students’ all-round development. By considering existing literature and potential areas for improvement, this study seeks to contribute to the advancement of physical education practices and the development of well-rounded students in the modern education system.